Perlindungan Hukum Terhadap Anak Korban Tindak Pidana Kekerasan Seksual (Studi Kasus Polres Gorontalo Kota) - ahmad, isnawir; Nur, Rafika; Jupri, Jupri; P, Umar (Unisan Law Review, 2025)
This study aims to determine: (1) How is the legal protection for child victims of violent crimes in the jurisdiction of the Gorontalo City Police? and (2) What are the inhibiting factors for legal protection for child victims of sexual violence in the jurisdiction of the Gorontalo City Police? This study uses an empirical legal research method, a legal research method that functions to see the law in a real sense and examine how the law works in the community environment. The results of this study indicate that: (1) Legal protection for child victims of TPKS is regulated in Law Number 34 of 2014 concerning Child Protection, but there are several weaknesses in this law, namely that it is not regulated more specifically regarding restitution and the increasing TPKS against children (2) Inhibiting factors in providing legal protection for child victims of TPKS are 2 factors, namely internal and external